MENINGKATKAN OPTIMALISASI PEMBERDAYAAN BUMDES MELALUI STRATEGI MANAJEMEN USAHA YANG MANDIRI DAN PROFESIONAL PADA BUMDES DI DESA WANADADI - Maesaroh, Siti; Saputra, Andi Wahyu; tono, Lus; Suryani, Ratna (STIE Pelita Nusantara, 2022)
This study aims to to find out how the strategy of independent and professional business management of Village-Owned Enterprises in increasing the optimization of empowerment in Wanadadi village, Wanadadi District, Banjarnegara Regency. The methods used in this devotion are through observation, material exposure and practice.The results of the team's service show that the development of Village-Owned Enterprises (BUMDes) benefits can be felt by the residents of Wanadadi Village, Wanadadi District, Banjarnegara Regency, namely with an independent and professional business management strategy that can increase the optimization of BUMDes empowerment optimization of community empowerment and also contribute to development and have a direct impact on the economy and culture of the community.Keywords: BUMDes, Optimization of Empowerment, Management Strategy